Drafted and served Edward "Skip" Swain ; one citizen soldier's experiences in Vietnam - Banks, Stephen A. (Banks, 2013)
The book was donated by the author in 2013 and is a memoir of Edward "Skip" Swain about his personal experiences in Vietnam as an enlisted man